Hypothyroidism complicates bradyarrhythmic episodes in a heart-transplanted patient: Can it be treated with low-dose dopamine? - Cingoz, Faruk (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Extracorporeal circulation decreases thyroid hormone levels in peripheral blood. This clinical entity may complicate the postoperative period after heart transplantation if the recipient has taken thyroid hormone replacement therapy. Cardiac transplantation was performed on a patient in whom thyroid hormone levels decreased after surgery. Sinus bradycardia was seen after surgery (30-40 bpm). Thyroid hormones were replaced in the patient. Due to the fact that temporary pacing decreased blood pressure, dopamine was safely given in very low doses. This case was discussed under the literature knowledge.